Cover Feature: Transport Matters: Boosting CO2 Electroreduction in Mixtures of [BMIm][BF4]/Water by Enhanced Diffusion (ChemPhysChem 22/2017). Issue 22 (7th November 2017) - Rudnev, Alexander V.; Fu, Yong‐Chun; Gjuroski, Ilche; Stricker, Florian; Furrer, Julien; Kovács, Noémi; Vesztergom, Soma; Broekmann, Peter
Abstract : The Cover Feature shows the broken balance of Earth's carbon cycle. Electroreduction is a possible route of decreasing atmoshperic CO2 . In ionic liquids, the addition of water boosts CO2 reduction by diffusion enhancement. More information can be found in the Full Paper by A. V. Rudnev et al. onpage 3153 in Issue 22, 2017 (DOI:10.1002/cphc.201700737 ).